Simile As An Effective Literary Device in the Vietnamese-English Translation Equivalent - Huu Chanh, Nguyen (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
Many Vietnamese writers have recognised the utility of literary devices to beautify the artistic features in written texts. Like other rhetorical devices, simile plays an essential role in bringing meaningful values close to the readers. The research aims at identifying the usage of simile in the translation equivalents between Vietnamese and English in De men phieu luu ky and its translated version Diary of a cricket. From analysing 108 sentences by the descriptive qualitative research, the findings showed that (1) The high frequency of using the complete form of simile to express the figure of speech. (2) The imbalance in the translation rate between two languages and the most popular simile word of like usage in English translated text. (3) The variables of comparative words and themes used in the target text show the same meaning in the source text. Those conclusions shed light on the quality improvement on the target text, especially in both translator's training and further translation education.